Metallic spintronic devices - Wang, Xiaobin (Boca Raton: CRC Press, 2015)
"Featuring contributions from well-known academic and industrial experts in the field, this book examines the latest research, development, and applications of metallic spintronic devices, from magnetic tunneling junction sensors and spin torque oscillators to spin torque memory and logic. Applying physics principles for practical implementations of spintronic devices, the text provides specific model, design, and processing procedures for current commercial and future devices. By addressing both mainstream and emerging metallic spintronic devices, the editor provides a balanced view of the state of the art"--
"A CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa plc."
Keywords: Spintronics -- Materials; Magnetic materials; Metals; TECHNOLOGY & ENGINEERING / Electronics / Circuits / General; TECHNOLOGY & ENGINEERING / Electronics / General; SCIENCE / Physics